Kontribusi penerapan model pembelajaran card sort berbasis pendekatan contextual teaching and learning terhadap peningkatan hasil belajar siswa dalam mata pelajaran Pendidikan Kewarganegaraan di kelas VII-C SMPN 1 Cadasari Pandeglang Banten - Aina Mulyana (Universitas Negeri Yogyakarta, 2010)
This article is based on a report of classroom action research (CAR) done among students of class VII C SMPN 1 Cadasari by implementation of Contextual Teaching and Learning (CTL) based Card Sort teaching model, and its contribution toward increase of students learning output in civic education Selecting class VII C as model class is based on consideration of low student learning outcomes of civic education. This note was taken from average of grades in report book and percentage of pass in test of last semester compared by other class. So that, Writer tries to conduct CAR by implementing CTL Card Sort teaching model to increase student learning outcomes of civic education. CAR is conducted by implementing action plan in the form of using some varied teaching model in class VII C. While in the other classes namely Class VIIA and Class VIIB as comparator classes, teaching model used is the conventional one although also based on CTL principles.Analysis process is done by analyzing daily test results to know progress of students learning outcomes and employ a Collaborator to observe and analyze excess and lack of researcher during teaching-learning process. The observation result from partner is used as reflection source and consideration to select following action. After four cycles of research and based on reflection with a Collaborator, it is resulted that using CTL based Card Sort teaching model can effectively increase students learning outcomes in subject matter of civic education. The result proves that CTL based Card Sort teaching model compared to other model has some advantages: a) relevant for ages of junior high school, b) simple and cheap, c) prioritizing collaboration, d) joyful and not boring, e) requiring mutual support, and f) encouraging student to be active.